Homeotic Function of Drosophila Bithorax-Complex miRNAs Mediates Fertility by Restricting Multiple Hox Genes and TALE Cofactors in the CNS. - Garaulet, D.L.; Castellanos, M.C.; Bejarano, F.; Sanfilippo, P.; Tyler, D.M.; Allan, D.W.; Sánchez-Herrero, E.; Lai, E.C. (Developmental Cell, 2014)
The Drosophila Bithorax complex (BX-C) Hox cluster contains a bidirectionally transcribed miRNA locus, and a deletion mutant (?mir) lays no eggs and is completely sterile. We show these miRNAs are expressed and active in distinct spatial registers along the anterior-posterior axis in the CNS. ?mir larvae derepress a network of direct homeobox gene targets in the posterior ventral nerve cord (VNC), including BX-C genes and their TALE cofactors. These are phenotypically critical targets, because sterility of ?mir mutants was substantially rescued by heterozygosity of these genes. The posterior VNC contains Ilp7+ oviduct motoneurons, whose innervation and morphology are defective in ?mir females, and substantially rescued by heterozygosity of ?mir targets, especially within the BX-C. Collectively, we reveal (1) critical roles for Hox miRNAs that determine segment-specific expression of homeotic genes, which are not masked by transcriptional regulation; and (2) that BX-C miRNAs are essential for neural patterning and reproductive behavior.